(untitled) (Sains Humanika, 2012)
Ibadah (worship) is important in human life. Its importance is clearly reflected in al-Quran which explains that the main purpose of man’s creation is to devote himself to Allah. Realizing this, counselors see the need to apply the element of ibadah in counseling as a method to resolve a client’s problem. Hence, this research is conducted to identify methods of applying ibadah in counseling. This research is a study survey. Selection of sampling is by convenience method (N=30). Data is collected from questionnaires and analyzed by descriptive statistics. The research outcome shows some methods of applying the element of ibadah in counseling such as ascertaining ibadah knowledge background of the client, identifying the relation between client’s problem with ibadah, identifying the type of ibadah suitable to be applied in counseling, identifying the counseling level suitable for applying ibadah and identifying suitable counseling skills necessary for applying ibadah in counseling.